Polyamide resin composition

By mixing aliphatic and amorphous polyamide resins into the polyamide resin, and adding inorganic reinforcement materials and metal hypophosphate salts to control the amide exchange reaction, the stability problem of the polyamide resin composition when the manufacturing conditions change is solved. A formed product with high strength, high rigidity and good appearance is achieved.

CN116507672BActive Publication Date: 2025-01-07TOYOBO MC CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202180081167.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-07
Filing Date
2021-11-26
Publication Date
2025-01-07
Estimated Expiration
2041-11-26

AI Technical Summary

Technical Problem

The conventional polyamide resin compositions are difficult to maintain high strength, high rigidity and good appearance when production conditions change, and are easily affected by manufacturing conditions, resulting in unstable characteristics of the molded product.

Method used

By mixing aliphatic polyamide resin and amorphous polyamide resin in the polyamide resin, and adding inorganic reinforcement materials and metal hypophosphate salts at high filling amounts, the early stage of the amide exchange reaction is controlled to reach the metastable polymer state, thereby stabilizing the Polymer structure improves the ability to resist changes to manufacturing conditions.

Benefits of technology

A molded product that maintains high strength, high rigidity and good appearance when manufacturing conditions change is realized, ensuring consistency and stability of the mechanical properties and appearance characteristics of the molded product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004261945400000101
    Figure BDA0004261945400000101
Patent Text Reader

Abstract

The present invention provides a polyamide resin composition that is less susceptible to changes in manufacturing conditions and can stably provide molded products with high rigidity and good appearance. A polyamide resin composition, characterized in that it contains 0 to 3 parts by mass of a metal hypophosphite (D) relative to 100 parts by mass of 20 to 60 parts by mass of an aliphatic polyamide resin (A), 5 to 20 parts by mass of a polyamide MXD6 resin (B) and 30 to 59 parts by mass of an inorganic reinforcing material (C), and the polyamide resin composition has an MFR of 3 to 60 g / 10 minutes measured under the conditions of a load of 2.16 kg and 275°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyamide resin composition, and more particularly to a polyamide resin composition containing reinforcing fibers at a high filling amount and capable of providing a molded product having high strength, high rigidity and excellent appearance. Background Art

[0002] Generally, aliphatic polyamide resins represented by polyamide 6 and polyamide 66 are excellent in mechanical strength, heat resistance, impact resistance, and chemical resistance, and are widely used in automobile parts, electrical parts, electronic parts, and household goods, etc. Among them, it is known that fiber-reinforced polyamide resin compositions to which inorganic reinforcing materials represented by glass fibers are added have greatly improved rigidity, strength, heat resistance, etc., and reinforcing materials such as glass fibers are added in large quantities (Patent Documents 1, 2, etc.).

[0003] However, if a large amount of reinforcing materials such as glass fiber are added, the appearance of the molded product is extremely degraded in many cases, and the product value is significantly impaired. Patent Documents 1 and 2 propose the use of low-viscosity polyamide resins, but the appearance of the molded product is not satisfactory. Therefore, Patent Document 3 proposes a method of using an amorphous semi-aromatic polyamide resin and a specific elastomer in addition to an aliphatic polyamide resin in order to improve the appearance of the molded product (Patent Document 3).

[0004] This method does improve the appearance, but has the disadvantages of reduced rigidity and heat resistance of the molded product. It is also easily affected by changes in manufacturing conditions, and has difficulties in manufacturing stability, making it difficult to obtain stable molded product characteristics.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 6-313045

[0008] Patent Document 2: Japanese Patent Application Publication No. 2007-112915

[0009] Patent Document 3: Japanese Patent Application Publication No. 2009-215534 Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] The present invention is proposed to solve the above-mentioned problems, and its object is to provide a polyamide resin composition that is less susceptible to changes in manufacturing conditions and can stably provide a molded product with a high reinforcing fiber content, high strength, high rigidity, good appearance and excellent high-temperature rigidity.

[0012] The present inventors have studied the reason for improving the appearance of a product because it is sometimes difficult to obtain a stable molded product with good appearance when different types of polyamide resins such as amorphous polyamide resins are mixed with crystalline aliphatic polyamide resins. As a result, it was found that the reason is that if the manufacturing conditions change, the progress of the transamide reaction between polyamides is prone to change. Therefore, if the transamide reaction can be progressed and reach a metastable polymer state at an early stage, it is difficult to be affected by the change of manufacturing conditions, thereby achieving the present invention.

[0013] Means for solving technical problems

[0014] That is, the present invention is as follows.

[0015] (1) A polyamide resin composition comprising 0 to 3 parts by mass of a metal hypophosphite (D) based on a total of 100 parts by mass of 20 to 60 parts by mass of an aliphatic polyamide resin (A), 5 to 20 parts by mass of a polyamide MXD6 resin (B), and 30 to 59 parts by mass of an inorganic reinforcing material (C);

[0016] The polyamide resin composition has an MFR of 3 to 60 g / 10 minutes as measured under the conditions of a load of 2.16 kg and 275° C.

[0017] (2) The polyamide resin composition according to (1), wherein the polyamide resin composition has a cooling crystallization temperature of 160 to 190°C.

[0018] (3) The polyamide resin composition according to (1) or (2), comprising 0.001 to 3 parts by mass of the metal hypophosphite (D) based on 100 parts by mass of the total of (A), (B) and (C).

[0019] (4) The polyamide resin composition according to any one of (1) to (3), characterized in that the polyamide resin composition contains 40 to 59 parts by mass of the inorganic reinforcing material (C) based on 100 parts by mass of the total of (A), (B) and (C).

[0020] (5) The polyamide resin composition according to any one of (1) to (4), wherein the inorganic reinforcing material (C) is glass fiber.

[0021] (6) The polyamide resin composition according to any one of (1) to (5), wherein the polyamide resin composition has an MFR of 4 to 25 g / 10 min as measured under conditions of a load of 2.16 kg and 275° C.

[0022] Effects of the Invention

[0023] The polyamide resin composition of the present invention is less susceptible to changes in production conditions and can stably provide molded products having high strength, high rigidity, good appearance, and excellent high-temperature rigidity. DETAILED DESCRIPTION

[0024] The present invention is described in detail below.

[0025] As the aliphatic polyamide resin (A) in the present invention, an aliphatic polyamide resin having an amide bond (-CONH-) in the molecule is preferred, and has a crystalline melting point. Specifically, polymers such as polycaprolactam (polyamide 6), polyhexamethylene adipamide (polyamide 66), polybutylene adipamide (polyamide 46), polyhexamethylene sebacamide (polyamide 610), polydodecane diamide hexamethylene diamine (polyamide 612), polylaurolactam (polyamide 12), poly-11-aminoundecanoic acid (polyamide 11), and copolymers and mixtures thereof, etc., can be cited, but are not limited thereto. In the present invention, as preferred aliphatic polyamide resin (A), polyamide 6, polyamide 66, and a mixture of polyamide 6 and polyamide 66 can be cited, and polyamide 6 is particularly preferred.

[0026] The relative viscosity of the aliphatic polyamide resin (A) (measured using 96% sulfuric acid and a polyamide resin concentration of 1 g / dl) is preferably in the range of 1.8 to 3.5, and more preferably in the range of 2.0 to 3.2.

[0027] The blending ratio of the aliphatic polyamide resin (A) is 20 to 60 parts by mass, preferably 25 to 50 parts by mass, and more preferably 28 to 42 parts by mass, relative to 100 parts by mass of the total of the aliphatic polyamide resin (A), the polyamide MXD6 resin (B) and the inorganic reinforcing material (C).

[0028] In the range of less than 20 parts by mass and more than 60 parts by mass, the effects of the present invention are difficult to be exhibited. In the present invention, the blending ratio directly constitutes the content ratio in the polyamide resin composition.

[0029] In the present invention, polyamide MXD6 resin (B) refers to a polyamide resin mainly composed of poly(m-xylylene adipamide), which is a polycondensate of a diamine component in which at least 80 mol% of the diamine component is m-xylylene diamine and a dicarboxylic acid component in which at least 80 mol% of the dicarboxylic acid component is adipic acid. As a diamine component other than m-xylylene diamine, when it is 20 mol% or less, p-xylylene diamine, tetramethylene diamine, hexamethylene diamine, etc. can be used. As a dicarboxylic acid component other than adipic acid, when it is 20 mol% or less, an aliphatic dicarboxylic acid such as sebacic acid can be used.

[0030] The relative viscosity of the polyamide MXD6 resin (B) (measured using 96% sulfuric acid and a polyamide resin concentration of 1 g / dl) is preferably in the range of 1.5 to 4.0, and more preferably in the range of 1.8 to 3.0.

[0031] The mixing ratio of the polyamide MXD6 resin (B) to 100 parts by mass of the total of the aliphatic polyamide resin (A), the polyamide MXD6 resin (B) and the inorganic reinforcing material (C) is 5 to 20 parts by mass, preferably 10 to 20 parts by mass, and more preferably 10 to 17 parts by mass. By the content in this range, the moldability is excellent, the appearance of the molded product is excellent, and the heat resistance of the molded product is excellent. In the range of less than 5 parts by mass and more than 20 parts by mass, it is difficult to exert the effect of the present invention.

[0032] Regarding the mixing ratio of the aliphatic polyamide resin (A) and the polyamide MXD6 resin (B), the polyamide MXD6 resin (B) is preferably 10 to 90 parts by mass, more preferably 10 to 70 parts by mass, further preferably 10 to 55 parts by mass, and more preferably 15 to 45 parts by mass relative to 100 parts by mass of the aliphatic polyamide resin (A). If it is less than 10 parts by mass, it is difficult to control the crystallization temperature, and if it exceeds 90 parts by mass, the glass transition temperature becomes high, so it is difficult to obtain a good appearance without increasing the mold temperature.

[0033] In the present invention, the inorganic reinforcing material (C) is the material that most effectively improves the physical properties such as strength, rigidity and heat resistance. Specifically, fibrous materials such as glass fiber, carbon fiber, aluminum oxide fiber, silicon carbide fiber, zirconium oxide fiber, whiskers such as aluminum borate and potassium titanate, needle-shaped wollastonite, milled fiber, etc. can be cited. In addition, in addition to this, there are also glass beads, glass flakes, glass balls, silicon dioxide, talc, kaolin, wollastonite, mica, aluminum oxide, hydrotalcite, montmorillonite, graphite, carbon nanotubes, fullerenes, zinc oxide, indium oxide, tin oxide, iron oxide, titanium oxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, red phosphorus, calcium carbonate, potassium titanate, lead zirconate titanate, barium titanate, aluminum nitride, boron nitride, zinc borate, aluminum borate, barium sulfate, magnesium sulfate, and layered silicates that have been organically treated for the purpose of interlayer peeling. Filling materials such as can also be used as inorganic reinforcing materials (C). Among them, glass fiber and carbon fiber are particularly preferably used. These inorganic reinforcing materials (C) may be used alone or in combination of two or more.

[0034] When using fibrous reinforcement as inorganic reinforcement (C), it is preferred that inorganic reinforcement treated with coupling agents such as organosilane compounds, organic titanium compounds, organic borane compounds and epoxy compounds in advance, and particularly preferably inorganic reinforcement that is easy to react with carboxylic acid groups or / and carboxylic anhydride groups. In the polyamide resin composition formed by mixing glass fibers treated with coupling agents, excellent mechanical properties and excellent appearance characteristics can be obtained, so it is preferred. In addition, in other fibrous reinforcements, when the coupling agent is not treated, it can also be added later for use.

[0035] When the inorganic reinforcing material (C) is glass fiber, it is preferred to use chopped strand-like fibers cut into a fiber length of about 1 to 20 mm. As the cross-sectional shape of the glass fiber, glass fibers with circular cross-sections and non-circular cross-sections can be used. As the cross-sectional shape of the glass fiber, glass fibers with non-circular cross-sections are preferred compared to the physical properties. As glass fibers with non-circular cross-sections, glass fibers with approximately elliptical, approximately oblong, and approximately cocoon-shaped cross-sections perpendicular to the length direction of the fiber length are also included, and the flatness is preferably 1.5 to 8. Here, flatness refers to the ratio of the long diameter / short diameter when the length of the long side of the rectangle is the long diameter and the length of the short side is the short diameter, assuming that the minimum area of ​​the rectangle circumscribed with the cross-section perpendicular to the length direction of the glass fiber is the ratio of the long diameter / short diameter. The thickness of the glass fiber is not particularly limited, but the short diameter is about 1 to 20 μm and the long diameter is about 2 to 100 μm.

[0036] The glass fiber is preferably treated with a coupling agent such as a silane-based or titanate-based agent, and it is particularly preferred to use a glass fiber treated with a silane-based coupling agent. Preferred silane-based coupling agents include γ-glycidyloxypropyl trimethoxysilane, γ-glycidyloxypropyl methyl diethoxysilane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, γ-anilinopropyl trimethoxysilane, γ-(2-aminoethyl)aminopropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, vinyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, and the like, and γ-glycidyloxypropyl trimethoxysilane, γ-anilinopropyl trimethoxysilane, γ-(2-aminoethyl)aminopropyl trimethoxysilane, and γ-methacryloxypropyl trimethoxysilane are particularly preferred.

[0037] The proportion of inorganic reinforcing material (C) relative to a total of 100 parts by mass of aliphatic polyamide resin (A), polyamide MXD6 resin (B) and inorganic reinforcing material (C) is 30 to 59 parts by mass. In addition, it is preferably 40 to 59 parts by mass, more preferably 45 to 59 parts by mass, and further preferably 50 to 59 parts by mass. When it is less than 30 parts by mass, there is a worry of insufficient rigidity, and when it is greater than 59 parts by mass, there is a worry of deterioration in the appearance of the molded product. As the proportion of inorganic reinforcing material (C), when it is 40 to 59 parts by mass, the balance between rigidity and molded appearance is particularly excellent, so it is preferred.

[0038] In the polyamide resin composition of the present invention, it is preferred to contain a metal hypophosphite (D). The metal hypophosphite (D) refers to a salt of hypophosphorous acid with elements of Groups 1, 2, 3, 4, 5, 6, 7, 8, 11, 12, and 13 in the periodic table, and metals such as tin and lead, and one or more combinations thereof can be used. Among them, from the viewpoint of being able to more significantly achieve the effect of the present invention, sodium hypophosphite (NaH2PO2)2 and calcium hypophosphite (Ca(H2PO2)2) are preferred. The metal hypophosphite may be a hydrate, and examples thereof include sodium hypophosphite monohydrate (NaH2PO2·H2O) and the like.

[0039] The amount of the metal hypophosphite (D) is preferably 0.001 to 3 parts by mass, more preferably 0.05 to 1.5 parts by mass, and still more preferably 0.08 to 0.8 parts by mass, relative to a total of 100 parts by mass of the aliphatic polyamide resin (A), the polyamide MXD6 resin (B), and the inorganic reinforcing material (C). Even without the metal hypophosphite (D), a molded product having high strength, high rigidity, and excellent high-temperature rigidity can be obtained, but when the metal hypophosphite (D) is present in a specific range, the amide exchange reaction between the crystalline aliphatic polyamide resin and the polyamide MXD6 is promoted, and the properties of the resin composition are stabilized, so it is preferred.

[0040] The polyamide resin composition of the present invention has an MFR (melt flow rate) of 3 to 60 g / 10 minutes, preferably 3 to 45 g / 10 minutes, more preferably 4 to 25 g / 10 minutes, further preferably 5 to 20 g / 10 minutes, and more preferably 5 to 15 g / 10 minutes, measured under the conditions of a load of 2.16 kg and 275°C. If the MFR is less than 3 g / 10 minutes, in the case of a thin-walled molded product, there is a situation where fluidity is insufficient, and if the MFR is greater than 60 g / 10 minutes, there is a tendency for the molded product to easily generate burrs. This MFR can be achieved by making the polyamide resin composition have the above-mentioned structure.

[0041] The polyamide resin composition of the present invention has an MFR of 4 to 25 g / 10 min measured under a load of 2.16 kg and at 275° C., which is excellent in fluidity and is preferred for obtaining a molded product having the effects of the present invention. Such MFR can be achieved by adjusting the composition of the polyamide resin composition.

[0042] The polyamide resin composition of the present invention preferably has a crystallization temperature of 160 to 190° C., more preferably 170 to 185° C., as determined by DSC measurement at a heating rate of 20° C. / min in accordance with JIS K 7121. If the crystallization temperature is less than 160° C., the curing rate is slow and the molding cycle may be too long, while if it exceeds 190° C., the appearance improvement effect of the molded product may be poor.

[0043] In addition, in the polyamide resin composition of the present invention, in addition to the above, as required, within the known range, a heat stabilizer, an antioxidant, an ultraviolet absorber, a light stabilizer, a plasticizer, a lubricant, a crystal nucleating agent, a mold release agent, an antistatic agent, a combination of a halogen flame retardant and antimony oxide, various phosphoric acid flame retardants, melamine flame retardants, inorganic pigments, organic pigments, dyes or other types of polymers can be added. The polyamide resin composition of the present invention preferably contains aliphatic polyamide resin (A), polyamide MXD6 resin (B), inorganic reinforcing material (C) and hypophosphite metal salt (D) in a total amount of 70% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more.

[0044] The method for producing the polyamide resin composition of the present invention is not particularly limited as long as it is a method capable of melt kneading. A single screw extruder, a twin screw extruder, a kneader, a Banbury mixer, a roller press, etc. can be used, and a twin screw extruder is preferably used. In the case of a twin screw extruder, it is preferred to premix the above (A), (B) and various additives, and the component (D) dissolved in water as required by a tumbler mixer or a Henschel mixer, etc., supply the premix from a main feeder, and supply the component (C) from a side feeder, and melt knead at a temperature range of 220 to 330°C. The polyamide resin composition that is discharged into cooling water in the form of strands after melt kneading is granulated into a length of about 1 to 10 mm by a granulator.

[0045] The polyamide resin composition of the present invention can be made into a molded product by a known molding method. The molding method is not limited and can be appropriately used in injection molding, blow molding, extrusion molding, foam molding, special-shaped molding, calendering molding, and other various molding methods. Among them, injection molding is preferred. The molded product consisting of the polyamide resin composition of the present invention is suitable for metal replacement parts in the fields of automobiles, electrical / electronic components, household products, etc. due to its high rigidity and excellent appearance. For example, it is suitable for door mirror parts or circuit breaker parts.

[0046] [Example]

[0047] Next, the present invention will be specifically described using Examples and Comparative Examples, but the present invention is not limited thereto. In addition, the measured values ​​and evaluations in Examples and the like were obtained by the following methods.

[0048] 1. Measurement and evaluation methods

[0049] (1) Relative viscosity (RV) of polyamide resin:

[0050] The viscosity was measured using an Ubbelohde viscometer at 25° C. using a 96% by mass sulfuric acid solution at a polyamide resin concentration of 1 g / dl.

[0051] (2) Cooling crystallization temperature (Tc2):

[0052] A DSC measuring apparatus (EXSTAR6000 manufactured by Seiko Instruments) was used. The temperature was raised to 300°C at a rate of 20°C / min under a nitrogen flow, maintained at this temperature for 5 minutes, and then lowered to 50°C at a rate of 10°C / min to measure the peak temperature of the observed crystallization peak.

[0053] (3) Melt flow rate (MFR):

[0054] The measurement was conducted in accordance with ISO 1133. The obtained pellets of the polyamide resin composition were dried to a moisture content of less than 0.1% by mass, and the measurement was conducted under the conditions of a measurement temperature of 275° C. and a load of 2.16 kg.

[0055] (4) Flexural strength and flexural modulus:

[0056] Measured in accordance with ISO-178.

[0057] (5) Charpy impact strength:

[0058] Measured in accordance with ISO-179-1eA.

[0059] (6) Heat deformation temperature:

[0060] The deflection temperature under load was measured at a load of 1.82 MPa in accordance with JIS K7191-2:2015.

[0061] (7) Evaluation method of molded product appearance:

[0062] As the appearance of the molded product, the mirror glossiness was measured and evaluated by the following method.

[0063] A molded product was produced using a mirror-finished mold of 100 mm × 100 mm × 3 mm (thickness) at a resin temperature of 280°C and a mold temperature of 80°C, and the glossiness at an incident angle of 60 degrees was measured in accordance with JIS Z-8714. A higher value indicates better glossiness.

[0064] The glossiness measurement results were evaluated according to the following criteria.

[0065] ◎:97 and above

[0066] ○: 95 or above, 97 or below

[0067] △: 90 or more, less than 95

[0068] ×: less than 90

[0069] 2. Raw materials used in Examples and Comparative Examples

[0070] [Polyamide resin]

[0071] A-1: Polyamide 6

[0072] Toyobo "Glamid T-800" (RV2.6)

[0073] B-1: Polyamide MXD6

[0074] Toyobo "Glamid T-600" (RV2.1)

[0075] B-2: Polyamide 6T6I

[0076] 6T / 6I=33 / 67 (mol%), Grivory G21 (RV2.0) manufactured by EMS

[0077] [Inorganic reinforcement materials]

[0078] C-1: Fiberglass

[0079] Nippon Electric Glass Co., Ltd., ECS03T-275H

[0080] C-2: Talc

[0081] Linhuacheng, Talcan Pawder PK

[0082] [Metal Hypophosphite]

[0083] D-1: Sodium hypophosphite

[0084] [Other additives]

[0085] E-1: Magnesium Stearate

[0086] E-2: Pigment

[0087] SUMIKA COLOR CO.,LTD.,EPC-840

[0088] [Examples 1 to 13, Comparative Examples 1 to 4]

[0089] As shown in Table 1 below, each component except the inorganic reinforcing material was premixed with a tumble mixer, and the premix was supplied from the main feeder of a twin-screw extruder (TEM-1008, L / D=40), and the inorganic reinforcing material was supplied from the side feeder to perform melt kneading (main barrel temperature 270°C, protrusion rate: 350kg / hr or 450kg / hr), and the strands of the resin composition discharged in a water bath were granulated with a strand cutter to obtain pellets of each resin composition.

[0090] The obtained resin composition pellets were dried and then evaluated by the above method. The results are shown in Table 1.

[0091] [Table 1]

[0092]

[0093] The resin compositions of the examples show that molded products with high strength, high rigidity, good appearance and excellent high temperature rigidity can be obtained. In particular, when the inorganic reinforcing material (C) is added in an amount of 40 to 59 parts by mass, the balance between rigidity and molded appearance is excellent.

[0094] As in Examples 1 and 2 (6 and 7, 8 and 9, 10 and 11), by containing a specified amount of metal hypophosphite, even if the discharge volume of the extruder changes significantly, the melt fluidity of the resin composition of the resin composition of the present invention changes little, the appearance of the obtained molded product is excellent, and the mechanical properties are also stable and excellent.

[0095] In Examples 4 and 5, which are systems not containing a metal hypophosphite, the inclusion of the polyamide MXD6 resin resulted in relatively small effects of discharge rate fluctuations, and improvement in the appearance of the molded product was confirmed.

[0096] In Comparative Examples 1 and 2, which do not contain polyamide MXD6 resin, the appearance of the molded product is significantly poor. In Comparative Examples 3 and 4, which contain polyamide 6T6I as an amorphous polyamide resin instead of polyamide MXD6 resin, although the appearance of the molded product is excellent, the rigidity, heat resistance, mechanical properties, etc. of the molded product are reduced. In addition, in Comparative Examples 3 and 4, the change in the physical properties of the resin composition when the discharge rate of the extruder is greatly changed is slightly greater than that in Examples 1 and 2.

[0097] Industrial Availability

[0098] The polyamide resin composition of the present invention is not easily affected by changes in production conditions and can stably provide molded products with high rigidity and good appearance. Therefore, it is suitable as a molding material for parts and molded products in the fields of automobiles, electric / electronic parts, household products, etc. that require high rigidity and good appearance.

Claims

1. A polyamide resin composition, characterized in that Contains an aliphatic polyamide resin A, a polyamide MXD6 resin B and an inorganic reinforcing material C, relative to a total of 100 parts by mass of the aliphatic polyamide resin A, the polyamide MXD6 resin B and the inorganic reinforcing material C, The invention comprises 20 to 60 parts by weight of the aliphatic polyamide resin A, 5 to 20 parts by weight of the polyamide MXD6 resin B, 30 to 59 parts by weight of the inorganic reinforcing material C, and 0.001 to 0.8 parts by weight of a metal hypophosphite D. The aliphatic polyamide resin A is at least one selected from polyamide 6, polyamide 66 or polyamide 46, The polyamide MXD6 resin B refers to a polyamide resin with poly(m-xylylene adipamide) as the main component, which is a condensation product of a diamine component in which at least 80 mol% of the diamine component is m-xylylene diamine and a dicarboxylic acid component in which at least 80 mol% of the dicarboxylic acid component is adipic acid; as a diamine component other than m-xylylene diamine, at least one selected from p-xylylene diamine, tetramethylene diamine, and hexamethylene diamine is contained in the range of 0 to 20 mol%, and as a dicarboxylic acid component other than adipic acid, an aliphatic dicarboxylic acid is contained in the range of 0 to 20 mol%; The polyamide resin composition has an MFR of 3 to 60 g / 10 minutes as measured under the conditions of a load of 2.16 kg and 275° C. 2 . The polyamide resin composition according to claim 1 , wherein the cooling crystallization temperature of the polyamide resin composition is 160 to 190° C. 3 . The polyamide resin composition according to claim 2 , wherein the cooling crystallization temperature of the polyamide resin composition is 160 to 177° C.

4. The polyamide resin composition according to claim 1, characterized in that The aliphatic polyamide resin A is contained in an amount of 20 to 50 parts by mass based on 100 parts by mass of the total of A, B and C.

5. The polyamide resin composition according to claim 1, characterized in that The polyamide MXD6 resin B is contained in an amount of 13 to 20 parts by mass based on 100 parts by mass of the total of A, B and C. The polyamide resin composition according to claim 1, comprising 0.08 to 0.8 parts by mass of the metal hypophosphite D based on 100 parts by mass in total of A, B and C.

7. The polyamide resin composition according to claim 1, characterized in that The polyamide resin composition contains 40 to 59 parts by mass of the inorganic reinforcing material C based on 100 parts by mass of the total of A, B and C.

8. The polyamide resin composition according to claim 1, characterized in that The polyamide resin composition contains 45 to 55 parts by mass of the inorganic reinforcing material C based on 100 parts by mass of the total of A, B and C.

9. The polyamide resin composition according to claim 1, characterized in that The inorganic reinforcing material C is glass fiber.

10. The polyamide resin composition according to any one of claims 1 to 9, characterized in that The polyamide resin composition has an MFR of 4 to 25 g / 10 minutes as measured under the conditions of a load of 2.16 kg and a temperature of 275° C.

Citation Information

Patent Citations

  • Production of reinforced polyamide resin composition

    JP1994313045A

  • High strength polyamide resin composition and its production method

    JP2007112915A

  • Glass-fiber-reinforced polyamide resin composition

    JP2009215534A

  • Filled polyamide molding materials

    CN101861357A

  • Resin composition, and pellet and molded product thereof

    CN103946311A